Conjugated molecular bridges: A new direction to escalate linker assisted QDSSC performance. (December 2019) - Kusuma, J.; Chandan, H.R.; Balakrishna, R. Geetha
Graphical abstract: Highlights: Conjugated molecule as efficient linkers for pre synthesized QDSSCs. Interminable conjugation, favourable molecular orbital ameliorate electron injection. Enhanced Voc due to interfacial electrostatic interactions. High mobility of aromatic system for enhanced efficiency. Abstract: Immobilizing quantum dots on an electron transport layer (ETL) is a very crucial step in the fabrication of quantum dot sensitized solar cells (QDSSC). Post-synthesis assembly of quantum dots (QDs) via aliphatic linkers has limited the device performance because of low and non-uniform coverage of QD sensitizers. This can result in intermediate surface trap states increasing the probability of exciton recombination. Therefore, we have designed a bi-phenyl aromatic linker 4′-mercapto-biphenyl-4′carboxylic acid (MBCA) that tethers QDs and ETL efficiently via SH and COOH groups respectively. The designed linker has enhanced the overall power conversion efficiency due to its interminable conjugation, and a favourable molecular orbital distribution inducing better electron injection rate. To enhance the photon collection efficiency and to apprehend the compatibility of QDs, cascading heterostructure of CdS/CdSe QDSSC devices were fabricated. The ligand linkage was confirmed via molecular spectroscopy (NMR and ATR-IR spectroscopy) and there performance studies like IV, IPCE, capacitance-voltage and impedance measurements were carried out. These studies clearly substantiates the augmentation of electron injection rate attributed to conjugated molecular bridges, assisting shift of fermi level of TiO2 and quick electron tunnelling.